PELATIHAN PEMBUATAN SERBUK JAMU INSTAN GUNA MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA DI DESA BANYUMENENG - Astutiningsih, Christina; Kristantri, Rika Sebtiana; Anggie, Erlyn Juanita; Zulfa, Salsabila Rizqi (Universitas Islam Malang, 2024)
Banyumeneng Village in Mranggen, Demak, became the target of community service. Many mothers and youths in this village only participate in social and religious activities, but they have not tried to increase their family income. The objective of this community service program is to increase the community's knowledge on how to make high-quality instant herbal powder that can be consumed by themselves or sold. The focus of this activity is to provide training on making instant herbal powder preparations using plant raw materials in the surrounding environment. The methods used are socialization, education, training and evaluation. This activity makes the community better understand how the surrounding plants can be used for health products. The results of the interview after the service of making instant herbal drinks, almost all participants understood the material provided with a percentage of understanding close to 97%. After the training, the community can make herbal powder independently, as shown by their enthusiasm for the material